Horn colour varieties of the Hungarian Grey cattle - Radácsi, Andrea; Bodó, Imre; Béri, Béla (Acta Agraria Debreceniensis, 2008)
The Hungarian Grey Cattle breed is a ‘success-story’ of the national genetic conservation work. Traits of the breed have been subjects of several research projects, although many relationships remained unclear. Our present research results were meant to call attention to a less emphasized trait of the breed: the different horn colour varieties. Research work was carried out in the Hungarian Grey stock of the Hortobágy Non-profit Company for Nature Conservation and Gene Preservation. Ratio of the three main horn colour varieties (white, ‘cardy’, green) were determined in the observed female, male and steer stocks. Our results showed no significant differences (P